2002
DOI: 10.1109/tcsi.2002.804542
|View full text |Cite
|
Sign up to set email alerts
|

On projection-based algorithms for model-order reduction of interconnects

Abstract: Model-order reduction is a key technique to do fast simulation of interconnect networks. Among many model-order reduction algorithms, those based on projection methods work quite well. In this paper, we review the projection-based algorithms in two categories. The first one is the coefficient matching algorithms. We generalize the Krylov subspace method on moment matching at a single point, to multipoint moment-matching methods with matching points located anywhere in the closed right-hand side (RHS). of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…They suggest to use a subset of the approximated poles as interpolation points. Another interesting method for interpolation point selection in the area of circuits and systems is related to series expansions based on orthonormal polynomials, such as Chebyshev polynomials, and to series expansions based on generalised orthonormal basis functions in Hilbert and Hardy spaces [38].…”
Section: Adaptive Schemes For the Rational Methodsmentioning
confidence: 99%
“…They suggest to use a subset of the approximated poles as interpolation points. Another interesting method for interpolation point selection in the area of circuits and systems is related to series expansions based on orthonormal polynomials, such as Chebyshev polynomials, and to series expansions based on generalised orthonormal basis functions in Hilbert and Hardy spaces [38].…”
Section: Adaptive Schemes For the Rational Methodsmentioning
confidence: 99%
“…The precision of the low order approximate model is of great importance since it determines whether the controller design is good or not. In the past few decades, significant research studies on model reduction have been reported, such as Krylov Subspace method [4], Pade approximation method [5] Shi'ang Qi is with the School of Huazhong University of Science and Technology, Hubei 430074, China (e-mail:15801299065@qq.com) approximation method [6], Dominant Poles method, Continued Fraction method [7], Gradual Waveform estimation method [8], Balance order reduction method, and so on. Though all these methods are suitable for linear systems, they are not useful to non-linear system.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that model reduction techniques with preservation of passivity mostly belong to the balanced truncation class [11][12][13] or are spectral interpolation-based methods [14][15][16]. In the case of projection-based Krylov methods the problem of preservation of passivity has been studied by several researchers; for an overview of existing approaches see [6,[17][18][19][20][21]. The problem with the Krylov-based passivity preserving methods is that they often assume a special descriptor state space setting that may not always be feasible [11].…”
Section: Introductionmentioning
confidence: 99%